Synthesis and characterization - Will, Stefan; et al. (Springer Verlag, 2009)
As compared to bulk materials, magnetic nanoparticles possess distinct magnetic properties and attempts have been made to exploit their beneficial properties for technical and biomedical applications, e.g. for magnetic fluids, high-density magnetic recording, or biomedical diagnosis and therapy. Early magnetic fluids (MFs) were produced by grinding magnetite with heptane or long chain hydrocarbon and a grinding agent, e.g. oleic acid [152]. Later procedures for MFs precipitated Fe/Fe of an aqueous solution with a base, coated the particles by oleic acid, and dispersed them in carrier liquid [161]. However, besides the elemental composition and crystal structure of the applied magnetic particles, particle size and particle size distribution determine the properties of the resulting MF. Many methods for nanoparticle synthesis including the preparation of metallic magnetic particles have been described in the literature. However, there still remain important questions, e.g. concerning control of particle size, shape, and monodispersity as well as their stability towards oxidation. Moreover, peptization by suitable surfactants or polymers into stable MFs is an important issue since each application in engineering or biomedicine needs special MFs with properties adjusted to the requirements of the system. In this chapter we address the different pathways for nanoparticle synthesis and preparation of MFs. First, characterization methods will be introduced which are discussed more in detail together with nanoparticle synthesis and preparation of MFs. © 2009 Springer-Verlag Berlin Heidelber